Style and S(t)imulation: Popular Magazines, or the Aestheticization of Postsoviet Russia - Helena Goscilo (Studies in 20th & 21st Century Literature, 2000)
The new Postsoviet genre of the glossy magazine that inundated bookstalls and kiosks in Russia's urban centers served as both an advertisement for a life of luxury and an advice column on chic style. Conventionalized signs of affluence, models of beauty, "educational" articles on topics ranging from the history and significance of ties to correct behavior at a first-class restaurant filled the pages of magazines intended to provide an accelerated course in etiquette, appearance, and appurtenances for Russia's newly wealthy. The lessons in spending, demeanor, and taste emphasized moneyed visibility. Despite their differing emphases, popular magazines all shared the new-found fascination with aesthetics as a mode of constructing a cynosural Postsoviet public identity.
Keywords: postsoviet Russia; Russian literature; first-class; aesthetics; etiquette; wealthy; magazines; public identity; identity